2010
DOI: 10.1002/ajmg.b.31067
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in the TPH1 and TPH2 regions are not associated with persistent ADHD in a combined sample of 1,636 adult cases and 1,923 controls from four European populations

Abstract: The tryptophan hydroxylase 1 and 2 (TPH1 and TPH2) genes encode the rate-limiting enzymes in the serotonin biosynthesis. Genetic variants in both genes have been implicated in several psychiatric disorders. For attention-deficit/hyperactivity disorder (ADHD) in children, the results are conflicting, and little is known about their role in adult ADHD patients. We therefore first genotype-tagged all common variants within both genes in a Norwegian sample of 451 patients with a diagnosis of adult ADHD and 584 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…A summary of genetic studies of adult ADHD was reported in Franke et al 32 in a comprehensive review. The literature about adult ADHD now comprises six meta-analyses of candidate genes in International multi-center persistent ADHD collaboration (IMpACT) samples, 33, 34, 35, 36, 37, 38 two SNP-GWAS, 39, 40 two CNV-GWAS 41, 42 studies and three reviews of pharmacogenetics studies. 30, 43, 44 No meta-analyses of biochemical studies of adult ADHD have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…A summary of genetic studies of adult ADHD was reported in Franke et al 32 in a comprehensive review. The literature about adult ADHD now comprises six meta-analyses of candidate genes in International multi-center persistent ADHD collaboration (IMpACT) samples, 33, 34, 35, 36, 37, 38 two SNP-GWAS, 39, 40 two CNV-GWAS 41, 42 studies and three reviews of pharmacogenetics studies. 30, 43, 44 No meta-analyses of biochemical studies of adult ADHD have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Marked neurodevelopmental influences of genomic imprinting set the stage for structural-physiological variation that affect cognition, emotion, and pathophysiology of ADHD (e.g., [24]). Nevertheless, although innumerable gene association studies have provided a huge amount of evidence for multi-involvement for neurotransmitters and metabolic enzymes (e.g., monoamine oxidase [MAO] or tryptophan hydroxylase [TPH]) in genetic predispositions for the disorder, the conflicting results, due to failure to obtain association, are rife [2527]. …”
Section: Introductionmentioning
confidence: 99%
“…The most consistent evidence for an association with ADHD exists for the DRD5 gene microsatellite (Squassina et al 2008) and the SLC6A3 gene variable tandem repeat (VNTR) at the 3 0 UTR (Stergiakouli and Thapar 2010;Gizer et al 2009). In contrast, very weak individual associations were reported for TPH1 (Gizer et al 2009;Johansson et al 2010) and SNAP25 (Gizer et al 2009;Forero et al 2009;Kim et al 2007), but the 3 0 UTR of the latter was significant in a recent meta-analysis (Gizer et al 2009). Each of these genes often showed a (Gizer et al 2009).…”
Section: Discussionmentioning
confidence: 93%